2005
DOI: 10.1111/j.1468-2982.2004.00897.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation Into Sleep Disturbance of Patients Suffering from Cluster Headache

Abstract: The new discoveries relating to cluster headache (CH) encouraged the study of the relationship of the hypothalamus to respiratory physiology and its comorbidity with sleep apnoea. The question is whether the apnoeas are more frequent during REM sleep and the desaturations could be involved as triggers of the cluster attacks. Furthermore, could the connection with the hypothalamus, already proved, be responsible for an alteration in the structure of REM sleep and a chemoreceptor dysfunction. We set out to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 30 publications
0
64
1
Order By: Relevance
“…Cluster headache has been associated with REM sleep and sleep-disordered breathing. A study of 37 cluster headache patients who underwent polysomnography identified an 8.4-fold increase in the incidence of obstructive sleep apnea relative to age-and gender-matched controls (58% vs 14%, respectively), and this risk increased over 24-fold among patients with a body mass index greater than 25 kg/m 2 [24]. This marked increase in the incidence of sleep apnea among cluster headache patients had been reported in earlier research [25,26], and treatment of sleep apnea had been observed to improve cluster headache control [25].…”
Section: Cluster and Other Trigeminal Autonomic Cephalalgiasmentioning
confidence: 97%
“…Cluster headache has been associated with REM sleep and sleep-disordered breathing. A study of 37 cluster headache patients who underwent polysomnography identified an 8.4-fold increase in the incidence of obstructive sleep apnea relative to age-and gender-matched controls (58% vs 14%, respectively), and this risk increased over 24-fold among patients with a body mass index greater than 25 kg/m 2 [24]. This marked increase in the incidence of sleep apnea among cluster headache patients had been reported in earlier research [25,26], and treatment of sleep apnea had been observed to improve cluster headache control [25].…”
Section: Cluster and Other Trigeminal Autonomic Cephalalgiasmentioning
confidence: 97%
“…When both factors are associated, the treatment of sleep apnea may result in reduction or total remission of clusters [8]. For this reason, Nobre et al have suggested that polysomnography (PSG) studies would be required to check the presence of OSA in patients with cluster headaches [9].…”
Section: Introductionmentioning
confidence: 99%
“…We couldn't detect any exacerbation of cluster headaches or chronic daily headaches in our patients, but a prevalence of 53.8% was reported for cluster headaches, which were approximately 8.4 times more common in OSAS, when compared with normal individuals [17]. This rate was reported as 42.8% for chronic daily headaches in patients with OSAS, as well [18].…”
Section: Discussionmentioning
confidence: 71%